Behavioral Expression of Contextual Fear in Male and Female Rats - Russo, Amanda S.; Parsons, Ryan G. (Frontiers in Behavioral Neuroscience, 2021)
The study of fear conditioning has led to a better understanding of fear and anxiety-based disorders such as post-traumatic stress disorder (PTSD). Despite the fact many of these disorders are more common in women than in men, the vast majority of work investigating fear conditioning in rodents has been conducted in males. The goal of the work presented here was to better understand how biological sex affects contextual fear conditioning and expression. To this end, rats of both sexes were trained to fear a specific context and fear responses were measured upon re-exposure to the conditioning context. In the first experiment, male and female rats were given context fear conditioning and tested the next day during which freezing behavior was measured. In the second experiment, rats were trained and tested in a similar fashion while fear-potentiated startle and defecation were measured. We found that males showed more freezing behavior than females during a fear expression test. The expression of fear-potentiated startle did not differ between sexes, while males exhibited more defecation during a test in a novel context. These data suggest that the expression of defensive behavior differs between sexes and highlight the importance of using multiple measures of fear when comparing between sexes.